Climate Change Awareness and Mental Health Impacts among Community College Students in Kathmandu - Adhikari, Laxmi; Timalsina, Umesh; Kafle, Rameshwor (Janajyoti Journal, 2025)
Growing climate change impact on mental health of human beings is a serious public health problem witnessingeverywhere of the universe. The study on mental health of young people is critical for knowledge generationprocess. The overall objective of the study is to examine awareness of climate change and its impact on reportedanxiety among community college students of Kathmandu. Cross-sectional explanatory research design isemployed with collecting information from 335 graduate students. Univariate, bi-variate and multivariateanalysis was performed. The study revealed that about 23 percent of students who learned about climate changefrom sources other than school, college, or media have reported anxiety symptoms. Multiple regression analysisshows that climate change awareness and anxiety, students who consider climate change a less significant issueare about 11 times more likely to have anxiety symptoms [OR=11.4 (5.1-17.9)] than those who view it as veryimportant in their lives. The study concludes that climate change awareness are critical factor for the self-reported anxiety symptoms of students of community college. While controlling the social factors, the climatechange awareness are most influencing factors for anxiety prevalence. This suggests that climatic factors needto be through appropriate strategic approach.